Prevalence and Clinical and Immunoviralogical Profile of Human Immunodeficiency Virus-Hepatitis B Coinfection among Children in an Antiretroviral Therapy Programme in Benue State, Nigeria - Anigilaje, Emmanuel Ademola (Hindawi Publishing Corporation, 2013)
Background. Nigeria has the world largest burden of paediatric HIV and is also highly endemic for Hepatitis B virus (HBV). However, relatively little is known regarding the prevalence of HBV-HIV coinfections among Nigerian children. Methods. A retrospective study among treatment naive HIV-infected children attending the pediatric clinic of the APIN Plus/Harvard PEPFAR program of the Federal Medical Centre, Makurdi, between June 2008 and June 2012. Results. The mean age of the 395 subjects studied was 7.53 ± 4.23 years. Thirty-one subjects (7.8%) were positive for HBV. No subject was HIV-HBV-HCV triply infected. Significantly higher HIV-HBC coinfections were found, in older subjects (11–15 years), subjects that did not receive nor complete Hepatitis B vaccinations, and subjects that had a severe immunosuppression of < 15% with respective P values of 0.00, 0.01, and 0.00. HIV-HBV co-infection did not significantly impact on other baseline characteristics including, gender, WHO clinical stage, median absolute CD4 count, mean viral load, median ALT, and hepatotoxicity. Conclusion. A high seroprevalence of HBV among this cohort of HIV-infected children contributes to the calls for pre-ART screening for HBV and the necessary paradigm shift in the ART nucleoside backbone to include agent(s) more dually effective against HIV and HBV.